Cesarean delivery rates using Robson classification system in Ireland: What can we learn?. (May 2019) - Crosby, David A.; Murphy, Martina M.; Segurado, Ricardo; Byrne, Fionnuala; Mahony, Rhona; Robson, Michael; McAuliffe, Fionnuala M.
Abstract: Objective: It has been proposed that the Robson Ten-Group Classification System be used as a global standard for assessing, monitoring and comparing cesarean delivery (CD) rates within and between maternity services. Our objective was to compare the change of CD rates within the 10-Group Classification System in our institution over 10 years. Study design: From 2005–2014 inclusive data was collected prospectively and all women were classified using the obstetric concepts and parameters described in the Ten-Group Classification System. Linear regression and weighted Least Squares regression analyses were used to analyze trends over time. Results: During 2005–2014 inclusive, 88, 004 mothers delivered 89, 649 babies ≥500 g. Over the 10 year period there was an increase in CD rate from 18.3% to 23.5%, with a linear increase in CD rate by 0.6% annually (95% CI:0.52, 0.75;p < 0.001). The main contribution to the increase in the CD rate was Group 2a (induced single cephalic nulliparous women at term), Group 2b (pre-labor single cephalic nulliparous women at term) and Group 5 (single cephalic multiparous women at term with a previous CD). No increase in CD rate was noted in Group 1 (single cephalic nulliparous women presenting in spontaneous labor at term). The percentage of women ≥35 years of age increased from 28.4% to 39.8% over the study period (0.98% per year; 95% CI:0.64, 1.33;p < 0.001). Conclusion: The driving force for the increase in CD in the National Maternity Hospital has been induction of labor and pre-labor CD in nulliparous women with a single cephalic pregnancy at term. This inevitably results in a larger population of women with a previous CD and therefore a secondary contribution to the increase in the overall CD rate.